Pattern of brain atrophy rates in autopsy-confirmed dementia with Lewy bodies - Nedelska, Zuzana; Ferman, Tanis J; Boeve, Bradley F; Przybelski, Scott A; Lesnick, Timothy G; Murray, Melissa E; Gunter, Jeffrey L; Senjem, Matthew L; Vemuri, Prashanti; Smith, Glenn E; Geda, Yonas E; Graff-Radford, Jonathan; et al. (Neurobiology of aging, 2015)
Dementia with Lewy bodies (DLB) is characterized by preserved whole brain and medial temporal lobe volumes compared with Alzheimer's disease dementia (AD) on magnetic resonance imaging. However, frequently coexistent AD-type pathology may influence the pattern of regional brain atrophy rates in DLB patients. We investigated the pattern and magnitude of the atrophy rates from 2 serial MRIs in autopsy-confirmed DLB patients (n = 20) and mixed DLB/AD patients (n = 22), compared with AD (n = 30) and elderly nondemented control subjects (n = 15), followed antemortem. DLB patients without significant AD-type pathology were characterized by lower global and regional rates of atrophy, similar to control subjects. The mixed DLB/AD patients displayed greater atrophy rates in the whole brain, temporoparietal cortices, hippocampus and amygdala, and ventricle expansion, similar to AD patients. In the DLB and DLB/AD patients, the atrophy rates correlated with Braak neurofibrillary tangle stage, cognitive decline, and progression of motor symptoms. Global and regional atrophy rates are associated with AD-type pathology in DLB, and these rates can be used as biomarkers of AD progression in patients with LB pathology.
Keywords: Aged; Hippocampus; demence s Lewyho tělísky; spánkový lalok; magnetická rezonanční tomografie; Aged, 80 and over; velikost orgánu; Atrophy; lidé; senioři; ženské pohlaví; Neurofibrillary Tangles; Disease Progression; Biomarkers; Alzheimerova nemoc; progrese nemoci; Magnetic Resonance Imaging; Female; mužské pohlaví; Organ Size; amygdala; Parietal Lobe; atrofie; Brain; mozek; senioři nad 80 let; pitva; kognice; Amygdala; Autopsy; Humans; Cognition; neurofibrilární klubka; biologické markery; Male; Temporal Lobe; temenní lalok; Lewy Body Disease; Alzheimer Disease; hipokampus